2015
DOI: 10.1542/peds.2015-1675
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Cutaneous Blastomycosis in a Child With Juvenile Idiopathic Arthritis on Infliximab

Abstract: Blastomyces dermatitidis is a dimorphic fungus endemic to much of North America, particularly the soils of the midwestern and southeastern United States. Human infection typically occurs through inhalation of airborne conidia, which can be followed occasionally by dissemination to the skin, bone, genitourinary system, and central nervous system. A hallmark of the pathogen is that it can cause disease in both immunocompetent and immunosuppressed populations. Blastomycosis is rare in pediatric patients, with cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Table shows the pediatric patients with IFIs that were identified through the literature review and were provided with the required information . Not surprisingly, most of these children were treated with IFX and the vast majority of these cases come from the US.…”
Section: Risk For Invasive Fungal Infections In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Table shows the pediatric patients with IFIs that were identified through the literature review and were provided with the required information . Not surprisingly, most of these children were treated with IFX and the vast majority of these cases come from the US.…”
Section: Risk For Invasive Fungal Infections In Childrenmentioning
confidence: 99%
“…In a review of the incidence of specific OIs among children with JIA, Coccidioides infection had an incidence rate at 0.021/100 patient- Table 2 shows the pediatric patients with IFIs that were identified through the literature review and were provided with the required information. [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Not surprisingly, most of these children were treated with IFX and the vast majority of these cases come from the US. Concomitant treatment with other immunosuppressive agents seems to play a crucial role as well.…”
Section: Risk For Invasive Fungal Infections In Childrenmentioning
confidence: 99%
“…Studies have shown that pediatric infections account for 3%‐11% of all blastomycosis cases . Cases describing primary cutaneous blastomycosis in children are limited to immunosuppressed patients . The patient in this case was previously healthy and denied systemic symptoms throughout the history of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…31 Clinical data on blastomycosis in the setting of TNF- α exposure is sparse and is limited to case reports. 20,59 Nevertheless, blastomycosis was listed in the 2008 warning issued by the Food and Drug Administration regarding increased risk of fulminant infections with endemic mycosis in patients receiving TNF inhibitor therapy. 20 …”
Section: Blastomycosis In Immunocompromised Hostsmentioning
confidence: 99%